S19 Molecular fingerprinting and metagenomic analysis reveals a polymicrobial element in patients with chronic obstructive pulmonary disease. (2nd December 2011) - Purcell, P J; Nelson, A; Fisher, A; Perry, J D; De-Soyza, A; Cummings, S P
Abstract : Introduction and objectives: Chronic obstructive pulmonary disease (COPD) patients commonly exhibit a multi-factorial pathology with neutrophilic inflammation and chronic obstructive bronchiolitis. COPD patients suffer episodes of pulmonary exacerbations. The role of bacteria in exacerbations has been investigated in COPD using culture-dependent techniques. Unlike cystic fibrosis (CF), there are few molecular studies describing the possibility of a microbial community in the COPD lung contributing to the pathogenesis of COPD. Methods: Nine clinically stable COPD patients attending the Freeman Hospital had a bronchoalveolar lavage fluid (BALF) taken. DNA extraction from these samples was performed using an Ultraclean ® Microbial DNA Isolation Kit. DNA obtained from these samples was then used as template for conventional PCR. Both primer sets used targeted the universal bacterial and fungal V3 variable regions of the 16S rRNA gene and 28S rRNA gene respectively with attachment of a GC-clamp. Amplicons were then run out for analysis by denaturing gradient gel electrophoresis (DGGE) performed on a DCode System (BIO-RAD). Microbial DNA extracted from all nine BAL samples was then sent for 454 pyrosequencing to perform metagenomic analysis. Results: Molecular fingerprinting of BAL analysis by DGGE produced a distinct number of bands in each sample strongly indicating the presence of a diverse microbial community in the COPD infected lung. This was also seen in culture negative patients. Migration of bands present at the top of the denaturing gradient suggests that the lungs of COPD patients are heavily colonised with bacteria that have a low GC content such as Haemophilus influenzae, Streptoccocus pneumoniae, and Moraxella catarrhalis . Metagenomic analysis of the nine BAL samples by 454 pyrosequencing supports this hypothesis by detecting numerous other bacterial taxa present. Conclusions: This preliminary study shows that the lungs of COPD sufferers are colonised with multiple species of bacteria and demonstrates that a complex microbial community is present. Metagenomic analysis performed demonstrates the key bacterial taxa which may be responsible for inducing the damaging inflammatory response and the differences in bacterial diversity shown in the nine patients studied. Thus a complex microbiota may elicit ongoing inflammation leading to lung function loss and destruction of the lung architecture.